(untitled) - Mannino, Michacl V. (Boston,NewYork, NY, 2007)
This book provides the foundation for the advanced study of individual database management systems, electronic commerce applications, and enterprise computing
Keywords: Database design.,Application software,Database management,Thiết kế cơ sở dữ liệu,Phần mềm ứng dụng,Quản lý cơ sở dữ liệu; Development.,Sự phát triển